Design and Development of a Wearable Device for Multi-Parametric Human Health Monitoring - Arabboev, Mukhriddin; Begmatov, Shohruh; Nosirov, Khabibullo (EAI Endorsed Transactions on Internet of Things, 2024)
INTRODUCTION: Wearable technology has emerged as a promising tool for continuous health monitoring, offering potential disease prevention and management benefits. However, existing devices often provide limited physiological data, hindering comprehensive health assessments. OBJECTIVES: This study aims to design and develop a wearable device capable of multi-parametric human health monitoring, focusing on vital indicators such as heart rate, body temperature, and physical activity. METHODS: A modular design approach was employed to integrate multiple biosensors into a compact wearable device. The collected data was processed by a microcontroller and transmitted wirelessly to a server. RESULTS: The developed wearable device demonstrated accurate and reliable measurement of target health parameters, with results comparable to existing prototypes in terms of functional capabilities. CONCLUSION: The proposed wearable device holds significant potential for enhancing personal health management by providing comprehensive and real-time health data. Future research will focus on expanding the device’s capabilities, improving battery life, and conducting long-term user trials.